1991
DOI: 10.1002/ardp.2503241114
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic properties of triamterene derivatives in the coronary artery ligated rat model

Abstract: Triamterene and several triamterene derivatives were tested for antiarrhythmic activity in the coronary artery ligated and reperfused (CAL-R) rat. The class-III antiarrhythmic drugs (+/-)-sotalol and amiodarone, the class-I antiarrhythmics lidocaine and quinidine as well as the potassium sparing diuretic amiloride were used as reference drugs. Triamterene at the highest dose (30 mumol/kg) revealed a 100% protection against ventricular fibrillation (VF), whereas at 10 mumol/kg no antiarrhythmic activity for tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Therefore, a parameter ApH was introduced, to allow for a systematic deviation of the local pH at the outer membrane surface from the pH of the bulk solution. Using: pH10 ,1 = pHeulk + ApH, (2) introduced into the expression for B (in Eq. 1), the data were fitted to Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a parameter ApH was introduced, to allow for a systematic deviation of the local pH at the outer membrane surface from the pH of the bulk solution. Using: pH10 ,1 = pHeulk + ApH, (2) introduced into the expression for B (in Eq. 1), the data were fitted to Eq.…”
Section: Resultsmentioning
confidence: 99%
“…For several triamterene derivatives, distinct effects on the excretion of Na t , K + and Mgt were observed in vivo [13,19]. In addition, certain triamterene derivatives exerted antiarrhythmic effects in the heart in both in vivo and in vitro studies [1,2]. In the present study, we were therefore interested in the sensitivity of rENaC to triamterene and several triamterene derivatives with distinct antikaliuretic profiles [13].…”
Section: Introductionmentioning
confidence: 99%
“…23 Triamterene can also reduce the incidence and duration of arrhythmias induced by either cardiac glycoside toxicity25 or reperfusion of ligated rat coronary artery. 26 Moreover, it has been reported that triamterene can increase the QT interval independently of plasma potassium concentration in humans. 27 The mechanisms by which triamterene exhibits cardiac electrophysiological effects are unknown.…”
mentioning
confidence: 99%
“…To further evaluate the antiarrhythmic properties of pteridine derivatives, selected compounds were tested in the coronary artery ligated and reperfused rat (CAL-R) (BUSCH 1989;BUSCH et al 1991a;NETZER 1991). Some compounds such as 4-benzyltriamterene could not be investigated following i.v.…”
Section: B) In Vivo Studiesmentioning
confidence: 99%
“…(0), triamterene (ill), and two benzyltriamterene derivatives [RPH 3007 (t? BUSCH (1989) performed electrophysiologic studies with 4-(amethylpiperazinobenzyl)triamterene using calf Purkinje and ventricular muscle fibers. (NETZER et al 1992c) prolong action potential duration (+26%) in guinea pig papillary muscle with only minor effects on V max (-4%), which is indicative of a class-III antiarrhythmic mechanism of action (U.…”
Section: B) In Vivo Studiesmentioning
confidence: 99%